Strengthening Public Participation in The Law-Making - Sukardi, Sukardi; Wardana, Dodi Jaya (JUSTITIA JURNAL HUKUM, 2022)
The legal character of a democratic law is identical to its main characteristic, namely the participation of all groups in society. If democracy is defined as the participation of members or groups in society, then this is tantamount to accepting the position that democracy is only possible when the existing groups of people have relatively balanced political power. If one group of people is too strong, then the life of democracy will be threatened. At least, democracy depends on the will of the rulers. Community participation or participation is part of the principles of democracy. One of the main prerequisites for realizing this participation is openness or transparency. The principle of openness contains at least two main elements that allow community participation to occur, namely: First, the right to know. This right is a fundamental right in a democracy. That is, all matters relating to the public interest, then the public should know it completely, correctly and accurately. Second, the right to think. After the public has access to information about what is the public's right to know it, then the right of the community is also to be involved in contributing in order to support government policies.